Self-catalyzed growth of Cu@graphdiyne core–shell nanowires array for high efficient hydrogen evolution cathode - Xue, Yurui; Guo, Yuan; Yi, Yuanping; Li, Yongjun; Liu, Huibiao; Li, Dan; Yang, Wensheng; Li, Yuliang (Nano energy, 2016)
Here we show that a high efficient hydrogen evolution reaction which was carried out on the in-situ growth of self-supported core-shell nanowires array consisting of graphdiyne as the shell and Cu as the core on Cu foams (Cu@GD NA/CF). Subject to potential cycling treatment in 0.5M H2SO4, the Cu@GD NA/CF exhibits highly catalytic activity for hydrogen evolution reaction with an onset overpotential of 52mV and a Tafel slope of 69mVdec−1. Our findings suggest that synergetic interaction between GD and Cu is crucial for the catalytic performance of the electrode. This electrode needs only overpotentials of 79 and 162mV to achieve catalytic current densities of 10 and 100mAcm–2, respectively, and maintains its catalytic activity for almost 20h. The attractive performances of such array make it promising candidate as a future high-performance catalyst for applications. The first GD based 3D carbon nanoarchitectures with well-defined porous network structures working as a highly active hydrogen evolution cathode is developed. Its excellent electrocatalytic activities, combined with low-cost, convenient and scale-up preparation process, make it promising candidate for practical and efficient energy applications. [Display omitted] •Cu@GD core–shell nanowire arrays are synthesized by self-catalyzing growth method.•The Cu@GD NA/CF exhibits greatly enhanced catalytic activity for hydrogen evolution.•Synergetic interaction between GD and Cu is crucial for the catalytic performance.